Analysis of Microstrip Antennas using The Volume Surface Integral Equation Formulation and the Pre-Corrected Fast Fourier Transform Method - Xiao, Ke; Li, Ya-Nan; Zhao, Fei; Chai, Shun-Lian; Mao, Jun-Jie (Applied Computational Electromagnetics Society Journal (ACES), 2022)
A rigorous and effective analysis based on the volume-surface integral equation (VSIE) formulation and pre-corrected-fast Fourier transform method (P-FFT) is presented for the problems of finite microstrip antennas which are modeled by combined conducting and dielectric materials. Several typical microstrip antennas and conformal microstrip antenna arrays are reconsidered; the comparisons of results from calculation and measurement validate the algorithm. Different feed methods are also considered to excite the antennas and conformal arrays. All the problems could be solved on a small computer with high efficiency and good precision.